The 1964 Western Europe Agricultural Situation Supplement no. 2 to the 1964 world agricultural situation (Washington DC Washington, U. S. Dept. of Agriculture, Economic Research Service., 1964)
This book explains how the Western Europe continues to exhibit strong overall economic growth as the region with the highest growth rate in the free world. Prospects are excellent for continued economic expansion in 1964 at a rate not much different, perhaps slightly lower, than in 1963, Growth in the gross domestic product in the European Economic Community (EEC) during 1964 may approximate 4 to 4.5 percent in real terms. Economic activity is expanding in the United Kingdom and Spain and continuing at a relatively high level in most of the other European countries.
lje 04/07/17
Loans
Keywords: Agricultural development